FENOMENA FEAR OF MISSING OUT (FOMO) DALAM PERILAKU KOMUNIKASI DIGITAL GENERASI Z - Rusli Rusli; Emil Fatra (Komunika : Jurnal Ilmiah Komunikasi, 2026)
The rapid development of social media has transformed the communication behavior of Generation Z, including the emergence of the Fear of Missing Out (FoMO) phenomenon, which refers to the anxiety experienced when individuals feel they are missing out on information, experiences, or ongoing social activities. This study aims to analyze the FoMO phenomenon in the digital communication behavior of Generation Z from a communication studies perspective. The research employed a qualitative approach using a phenomenological design. Informants were selected through purposive sampling based on the following criteria: Generation Z individuals aged 18–27 years, active users of social media, and those who had experienced FoMO. Data were collected through in-depth interviews, non-participant observation, and document analysis, and were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing and verification. The findings identified five major themes: dependence on digital connectivity, anxiety about missing information, changes in interpersonal communication patterns, identity construction and social validation, and the impact of FoMO on digital well-being. The results indicate that FoMO encourages Generation Z to remain constantly connected to social media, intensifies information-checking behavior, accelerates communication responses, and promotes active participation in digital communities. On the other hand, FoMO also has negative consequences, including digital fatigue, decreased concentration, poor time management, and anxiety when access to social media is unavailable. This study confirms that FoMO is a communication phenomenon that influences interaction patterns, digital identity formation, and the quality of communication among Generation Z.